DYNAMICS OF RUNNING THE NUMBER OF ABORTIONS IN OMSK REGION FOR THE LAST YEARS - Роман Андреевич Моргунов; Елена Николаевна Кравченко (The Publishing House Medicine and Enlightenment, 2018)
The aim of the study - to analyze the dynamics of abortion in the Omsk region in recent years in comparison with indicators of the Russian Federation and the Siberian Federal district. Materials and methods: the study analyzed data of the official statistics of abortions for 2005-2015 has been applied the epidemiological method of research. Results. The results of the study showed that the frequency of abortions depending on the age of women in the Russian Federation as a whole has a positive trend. The highest percentage reduction in the number of abortions since 2005 and 2015 amounted to 81.2 % in the 15-19 age group. The highest percentage reduction in the number of abortions in the Siberian Federal district as in the whole of the Russian Federation from 2005 to 2015 is observed in the age group 15-19 years was 79.2 %. When assessing the frequency of abortions depending on the age of women in the Omsk region is certainly clearly seen their decline, but at the same time, the pace of decline in the frequency of abortions is quite low and the greatest number of abortions occur in the age of 20-34 years and the largest percentage reduction in the number of abortions in the Omsk region and in the whole of Russia, Siberian Federal district from 2005 to 2015 is observed in the 15-19 age group and was equal to 88.2% Conclusions. The study showed that the frequency of abortions has been steadily declining, which is a positive thing, but the rate of decline in frequency of abortions remains insufficient, because the figures are great. Most abortions occur in the age of 20-34 years, namely the most favorable period for pregnancy, which is a very negative factor for demography in General.